Teaching Profession and Satisfaction: A Female Perspective - Ghimire, Durga (Sotang, Yearly Peer Reviewed Journal, 2022)
Teachers are role models for educational improvement. Quality of education depends upon the provider and facilitator’s ability. The issue of this study is focused on the teaching profession and satisfaction from a female perspective. To explore the views on the teaching profession from a female teacher’s perspective and dig- out the affective reasons for teachers regarding professional satisfaction. This study talks about the female teacher profession's situation and their happiness with the quality of education they provide. This study is based on a qualitative research design. Purposefully selected three permanent female teachers of different community schools in Kathmandu Valley. To fulfill the objective of the study, I developed the interview it has used in-depth interviews with secondary female teachers for data collection. Every of my participants have stated that they are very glad and equally satisfied by their professions. There are many reasons behind it the major being an independent respectful and self-earning person. The profession in itself comes with huge respect and good social status in a community. Being respected by the children by their guardians and people of the community makes them self-satisfied and continue to do what they do. From the collected data teachers expressed their strong opinions regarding the teaching.